2021
DOI: 10.1177/2309499020988176
|View full text |Cite
|
Sign up to set email alerts
|

Personal protective equipment usage, recycling and disposal among spine surgeons: An Asia Pacific Spine Society survey

Abstract: Purpose: In this study we investigated on the personal protective equipment (PPE) usage, recycling, and disposal among spine surgeons in the Asia Pacific region. Methods: A cross-sectional survey was carried out among spine surgeons in Asia Pacific. The questionnaires were focused on the usage, recycling and disposal of PPE. Results: Two hundred and twenty-two surgeons from 19 countries participated in the survey. When we sub-analysed the differences between countries, the provision of adequate PPE by hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Likewise, PPE implementation barriers reported by studies from LMICs mainly indicate poor infrastructure in HFs 32 and no access to PPE. 18,83 PPE is strongly associated with increased risk of COVID-19 infection. Global PPE shortages during the pandemic has been widely reported, 101,102 with increases in demand for medical masks and a breakdown in the global supply chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, PPE implementation barriers reported by studies from LMICs mainly indicate poor infrastructure in HFs 32 and no access to PPE. 18,83 PPE is strongly associated with increased risk of COVID-19 infection. Global PPE shortages during the pandemic has been widely reported, 101,102 with increases in demand for medical masks and a breakdown in the global supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…. HFs adopted solutions such as respirator reuse without any decontamination and reprocessing process or protocols, 44,61,64,81,83 contrary to international recommendations. 104 LMICs have been most severely affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current PPE need has also affected other enterprises dependence upon PPE, including structure, installation, oil and gas energy, shipping, firefighting, and food outcome. As a result, there has been unprecedented acceleration in the use of PPE [4] , [5] , [6] , [7] , [8] . As the predominance of COVID-19, medical waste production, such as gowns, inspection kits, plastic boxes, and syringes after discovering the COVID-19 vaccine, has been grown worldwide is a notable warning to the climate and public well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Soon, various problems with a substantial impact on the working environment and staff safety appeared related to the availability, use, rationing, modification, compliance and recycling of PPE ( 7 , 10 , 11 , 12 ). Later, it was also observed that PPE might cause problems to surgeons of certain specialties and adversely affect their surgical performance, for example, due to a negative impact on vision and communication ( 13 , 14 , 15 , 16 , 17 ).…”
mentioning
confidence: 99%